CXCR4 promotes the growth and metastasis of esophageal squamous cell carcinoma as a critical downstream mediator of HIF‐1α. Issue 3 (17th January 2022) - Wu, Xianxian; Zhang, Hongdian; Sui, Zhilin; Gao, Yongyin; Gong, Lei; Chen, Chuangui; Ma, Zhao; Tang, Peng; Yu, Zhentao
Abstract: C–X–C motif chemokine receptor 4 (CXCR4) belongs to the CXC chemokine receptor family, which mediates the metastasis of tumor cells and promotes the malignant development of cancers. However, its biological role and regulatory mechanism in esophageal squamous cell carcinoma (ESCC) remain unclear. Here, we found that CXCR4 expression was associated with lymph node metastasis and a poor prognosis. In vitro and in vivo studies demonstrated that CXCR4 overexpression promoted ESCC cell proliferation, migration, invasion, and survival, whereas silencing CXCR4 induced the opposite effects. Mechanically, HIF‐1α transcriptionally regulates CXCR4 expression by binding to a hypoxia response element in its promoter. HIF‐1α‐induced ESCC cell migration and invasion were reversed by CXCR4 knockdown or treatment with MSX‐122, a CXCR4 antagonist. Collectively, these data revealed that the HIF‐1α/CXCR4 axis plays key roles in ESCC growth and metastasis and indicated CXCR4 as a potential target for ESCC treatment. Abstract : The current research data suggest that HIF‐1α/CXCR4 may serve as potential therapeutic target for ESCC patients. HIF‐1α enhances transcriptional activity of CXCR4 through binding to its promoter hypoxia response element sites.